Review of the Infrastructure Reconstruction Process in Cambodia - Tomasz LUKASZEWSKI; Kerry SLATTERY (Communications of International Proceedings, 2020)
For almost thirty years Cambodia has been rebuilding and expanding the infrastructure destroyed during decades of war, and striving to improve the quality of services provided by these facilities. The success of the measures taken is a prerequisite for achievement of the strategic goals including poverty alleviation and raising the citizens living standards, as well as maintaining economic growth and ensuring further development of the country. The article presents an assessment of progress in reconstruction across various sectors of physical infrastructure such as roads, railways, telecommunication networks, water supply facilities, irrigation systems, and electricity supply facilities made in Cambodia between years 1991-2018. The aim of the study is to evaluate the achieved level of development of the infrastructure assets in relation to its initial state, to the objectives adopted and to the expenses incurred for this purpose. The research used descriptive method and quantitative data obtained from documents published by public entities.
Keywords: Infrastructure; Cambodia; Development; Public Investment; Private Investment.